KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI MODEL PBL DAN MODEL TAPPS PADA SISWA KELAS X - Izzata, Fi'ina; Asmara, Adi (Universitas Muhammadiyah Bengkulu, 2020)
This study was aimed to know the differences in students' mathematical problem solving skills in problem basedlearning models with cooperative type thinking aloud pairs problem solving with a scientific approach at SMA Negeri 7 Bengkulu. Thedesign of this research was a quasi-experimental, used a pre-test post-test control group design. The population in this study were all students of class X MIPA SMA Negeri 7 Bengkulu consist of 6 classes, with samples consist of 3 classes, the first experimental class with the problem based learning model, the second experimental class cooperative learning model type thinking aloud pairs problem solving and conventional learning as a control class. The sampling technique used simple random sampling. Data collection was done by using a test of students' mathematical problem solving skills. The results of the research data were analyzed using one-way ANAVA test and BNT test. The prerequisite test used the Kolmogrove-Smirnov test to see normality and Bartlet's test to see homogeneity. The significant level used is 0.05. The research data showedÂ that there was a significant difference in students' mathematical problem-solving ability in the learning model of Problem Based Learning, cooperative type thinking aloud pairs problem solving in SMA Negeri 7 Bengkulu, and problem based learning learning model which gives better results compared to the thinking type cooperative learning model thinking aloud Pairs problem solving at SMA Negeri 7 Bengkulu.Keywords: mathematical problem solving, PBL,TAPPS